«LOVE THE TRUTH AND NEVER GIVE IT UP» THE ROLE OF M. KOVALEVFSKIY IN FORMING OF Р. SOROKIN'S SCIENTIFIC OUTLOOK - V. V. Vasilenko (Гуманитарные и юридические исследования)
The article studies Kovalevskiy's contribution to the development of Russian positivism and its influence on Sorokin's scientific outlook.